Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration. (6th November 2020) - Fer, Istem; Gardella, Anthony K.; Shiklomanov, Alexey N.; Campbell, Eleanor E.; Cowdery, Elizabeth M.; De Kauwe, Martin G.; Desai, Ankur; Duveneck, Matthew J.; Fisher, Joshua B.; Haynes, Katherine D.; Hoffman, Forrest M.; Johnston, Miriam R.; et al.
Abstract: In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century. Abstract : Model‐data integration demands of the ecological community, managers, policymakers and the society are becoming increasingly diverse and complex. A new strategy is needed to approach challenges in reducing the informatics bottlenecks to process ecological information, involving the whole research community to play an active role in confronting models with data and advancing our ecological understanding. We argue that a major step towards achieving ecological model‐data integration in a way that is transparent, easily communicable, and scales up to the size and diversity of the ecological community lies in the development and support of community‐wide cyberinfrastructure.